Protein arginine methyl transferase 1– and Jumonji C domain‐containing protein 6–dependent arginine methylation regulate hepatocyte nuclear factor 4 alpha expression and hepatocyte proliferation in mice. Issue 3 (24th January 2018) - Zhao, Jie; Adams, Abby; Roberts, Ben; O'Neil, Maura; Vittal, Anusha; Schmitt, Timothy; Kumer, Sean; Cox, Josiah; Li, Zhuan; Weinman, Steven A.; Tikhanovich, Irina
Abstract : Alcohol is a well‐established risk factor for hepatocellular carcinoma (HCC), but the mechanisms by which it promotes liver cancer are not well understood. Several studies have shown that cellular protein arginine methylation is inhibited by alcohol. Arginine methylation is controlled by the reciprocal activity of protein arginine methyltransferases, primarily protein arginine methyl transferase 1 (PRMT1), and a demethylase Jumonji C domain‐containing protein 6 (JMJD6). The aim of this study was to explore the role of arginine methylation changes in alcohol pathogenesis. We found that PRMT1 activity is inhibited in livers of mice fed with alcohol compared to pair‐fed mice. Using hepatocyte‐specific PRMT1 knockout mice, we identified that loss of PRMT1 results in enhanced hepatocyte proliferation and a 33% increase in liver size. This increased hepatocyte proliferation was associated with reduced expression of hepatocyte nuclear factor 4 alpha (Hnf4α), an important regulator of liver tumorigenesis. We found that PRMT1 regulates Hnf4α expression directly through arginine methylation at the (Hnf4α) promoter. In the absence of PRMT1, JMJD6 can demethylate the Hnf4α promoter and suppress its expression. We were able to restore Hnf4α expression and abolish the increase in hepatocyte proliferation by knockdown of JMJD6 in PRMT1 knockout mice. Knockdown of JMJD6 in alcohol‐fed mice similarly increased Hnf4α expression. We then examined whether loss of arginine methylation might play a role in alcohol‐associated liver cancers. We examined 25 human HCC specimens and found a strong correlation (R = 0.8; P < 0.01) between arginine methylation levels and Hnf4α expression in these specimens, suggesting that the above mechanism is relevant in patients. Conclusion: Taken together, these data suggest that PRMT1 inhibition, such as induced by alcohol, may result in epigenetic changes leading to loss of Hnf4α. This effect may contribute to alcohol's ability to promote liver tumors. (Hepatology 2018;67:1109–1126)